Global Research Trends of Acne (Acne Vulgaris) in Adolescents and Its Implications for Quality of Life: A Bibliometric Study - Riski Agustina Firdausi; Riyadatus Solihah (The Indonesian Journal of General Medicine, 2026)
Introduction: Acne vulgaris is a pervasive chronic inflammatory skin condition that disproportionately affects adolescents, often leading to profound psychosocial distress. Despite extensive clinical research, the integration of patient-centered outcomes and health literacy within the global research landscape remains fragmented. This study aims to map the intellectual structure and trends of adolescent acne research and its impact on quality of life. Methods: A comprehensive bibliometric analysis was conducted using data from the Web of Science Core Collection and Scopus (1990–2024). Science mapping was performed using VOSviewer and Biblioshiny to analyze publication trends, influential contributors, and thematic clusters. Results: Research output has grown exponentially since 2014, with the United States and Western Europe as primary hubs. Four thematic clusters were identified: (1) Clinical Foundations, (2) Psychosocial Impact, (3) Digital Health Literacy, and (4) Emerging Therapeutic Frontiers (Microbiome/Nanotechnology). Prevalence has increased significantly, particularly in lower-middle SDI regions, with females exhibiting higher rates. Discussion: The findings reveal a "research silo" between clinical dermatology and psychosocial health. Literature suggests a severe impact on self-esteem and suicidal ideation, yet standardized quality of life measures (DLQI, CADI) remain inconsistently applied. The rise of social media has introduced a new "vulnerability nexus" where misinformation thrives. Conclusion: Integrated, culturally contextualized interventions that address both clinical severity and digital health literacy are essential. Future research should prioritize bridging the gap between biological treatments and patient-reported outcomes.